Aplikasi Pembelajaran Pahlawan Melayu - JAMALUDIN, MUHAMMAD HAZIQ; MOHD AZMAN, NA'IM SYAKIR; NOOR AZIMI, NOOR SUHAIRI KHUZAIMI; IBRAHIM, ZURAIDA (Multidisciplinary Applied Research and Innovation, 2024)
This project aims to produce a learning application that provides user information of Pahlawan Melayu such as their struggle stories and images of the heroes. This aims to provide exposure to users so that they can know the history of the Pahlawan Melayu who have served the Tanah Melayu once upon a time. The problem faced is that the current generation does not recognize the Pahlawan Melayu who have contributed to the past. Perhaps only a few can answer the names of Pahlawan Melayu if asked by today’s generation. In addition, the interest in reading books among the younger generation is decreasing because it is more focused on the advancement of technology. The objective of this project is to identify and analyze relevant information to glorify the Pahlawan Melayu, develop an informative application for Malaysians to learn about the Pahlawan Melayu as well as test the effectiveness of the Malay Warrior Application (Aplikasi Pembelajaran Pahlawan Melayu). The methodology we chose is the ADDIE model. The ADDIE approach involves 5 important stages which are analyze, design, develop, implement and evaluate. The chosen project management methodology will determine how our work is prioritized and completed. This application contains 10 Pahlawan Melayu that have been selected according to each state. The narration of history is in the form of writing and contains the image of the hero. There are also mini games and quizzes to test the user’s level of understanding after exploring the history of the Pahlawan Melayu. In conclusion, this application will help our current generation to recognize Pahlawan Melayu more effectively. This is because they are more interested in using applications that have an element of learning because they display an interface that is attractive and fun to use. It also allows them to fill their time with beneficial activities.